Constraining the time of extinction of the South American fox Dusicyon avus (Carnivora, Canidae) during the late Holocene - Prevosti, Francisco Juan (2011)
The mass extinction at the end of the Pleistocene affected South America during the Late Pleistocene and the Early Holocene, when megamammals and large mammals disappeared. Several carnivores became extinct, like the sabretooth (Smilodon), the short face bear (Arctotherium) and some large canids (i.e. Protocyon, Canis dirus). After this mass event virtually no carnivores became extinct in South America. The only exception is the fox Dusicyon avus, a medium sized canid (estimated body mass between 10-15 kg) with a more carnivore diet than the living South American foxes (i.e. Lycalopex culpaeus). The last record of the species comes from middle-late Holocene archaeological sites in the Pampean Region (Argentina) and Patagonia (Argentina and Chile). During the Late Pleistocene D. avus had a wide distribution, which covered part of Uruguay, Argentina (Buenos Aires province) and the southern Patagonia. Albeit some remains from late Holocene sites have been published, these remains are still lacking absolute dating to determine the approximate date of extinction of this fox. In this contribution we present several new records from the Pampean and Patagonia regions, and several taxon dates. The new records indicate that D. avus survived in the late Holocene at least until ≈ 3000 radiocarbon years BP in the Isla Grande de Tierra del Fuego (Patagonia) and the continent. Since at this time humans were occupying most of the Pampas and Patagonia a revision of the causes behind the extinction of this fox is needed.